Gluteal Compartment Syndrome following Vascular and Neurological Injuries - Mahmoud A. Hafez; Moustafa Radwan (Case Reports in Medicine)
Gluteal compartment syndrome is a serious but rare condition that has recently been increasingly reported in literature. This report presents two cases that followed neurological and vascular injuries (first case: an injury of the superior gluteal artery; second case: neurological injury bilaterally). A high index of suspicion and attention is needed to early diagnose this condition due to the possibility of developing serious and potentially fatal complications and difficulty in management.